2013
DOI: 10.1111/1750-3841.12154
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Integrated Treatment of UV light and Low‐Dose Gamma Irradiation on Inactivation of Escherichia coli O157:H7 and Salmonella enterica on Grape Tomatoes

Abstract: The study evaluated the efficacy of integrated ultraviolet-C light (UVC) and low-dose gamma irradiation treatments to inactivate mixed strains of Escherichia coli O157:H7 and Salmonella enterica on inoculated whole grape tomatoes. A mixed bacterial cocktail composed of a 3 strain mixture of E. coli O157:H7 (C9490, E02128, and F00475) and a 3 serotype mixture of S. enterica (S. Montevideo G4639, S. Newport H1275, and S. Stanley H0558) was used based on their association with produce-related outbreaks. Spot inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…UV's effectiveness to reduce bacterial contamination on produce has been documented (Chun et al, 2010;Escalona et al, 2010;Sommers et al, 2010;Yaun et al, 2004). Mukhopadhyay et al, (2013) is likely that not all spots on the tomatoes will be directly exposed to the UV light as tomatoes will be rolling on the conveyer belt. Thus, effectiveness of UV-C light in reducing Salmonella contamination on different locations on tomato surfaces needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…UV's effectiveness to reduce bacterial contamination on produce has been documented (Chun et al, 2010;Escalona et al, 2010;Sommers et al, 2010;Yaun et al, 2004). Mukhopadhyay et al, (2013) is likely that not all spots on the tomatoes will be directly exposed to the UV light as tomatoes will be rolling on the conveyer belt. Thus, effectiveness of UV-C light in reducing Salmonella contamination on different locations on tomato surfaces needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 compares findings from this study with reported radiation resistance data ( D 10 value) or Salmonella treated with ionizing radiation alone and in combination with UV‐C or 1% calcium chloride (CaCI 2 ). In general, these studies, except for Moreira et al (2012) and Mukhopadhyay et al (2013), obtained higher D 10 values. One explanation is that their DUR values were higher than the ones reported in our study, and therefore their experimental set up was not optimal.…”
Section: Resultsmentioning
confidence: 81%
“…Pathogens were effectively reduced with aerosolized malic acid without degradation of quality. Moreover, Mukhopadhyay (Mukhopadhyay et al, ) observed no change in firmness and color of tomato with UV‐C radiation. Sensory results of this study were similar to these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Wong (Wong et al, 1998) reported a 1.5 and 2.0 log reduction of E. coli and S. Senftenberg when they were exposed to 1 kg/s 3 and 0.8 kg/s 3 doses of UV-C, respectively. Additionally, E. coli and Salmonella on grape tomatoes were reduced by <4 log using UV in combination with gamma irradiation (Mukhopadhyay, Ukuku, Fan, & Juneja, 2013). Cond on-Abanto (Cond on-Abanto, Cond on, Raso, Lyng, & Alvarez, 2016) showed a 4 log reductions of Lactobacillus plantarum and S. Typhimurium with UV-C treatment on flour powder.…”
Section: Resultsmentioning
confidence: 99%